2009
DOI: 10.1007/s10533-009-9374-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of structural chemistry and isotopic signatures of refractory soil organic carbon fraction isolated by wet oxidation methods

Abstract: Accurate quantification of different soil organic carbon (SOC) fractions is needed to understand their relative importance in the global C cycle. Among the chemical methods of SOC fractionation, oxidative degradation is considered more promising because of its ability to mimic the natural microbial oxidative processes in soil. This study focuses on detailed understanding of changes in structural chemistry and isotopic signatures of SOC upon different oxidative treatments for assessing the ability of these chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 64 publications
3
41
0
Order By: Relevance
“…The SOC fraction resistant to chemical treatment was assumed to be stabilized due to strong chemical interaction with soil minerals. From a comparison of different oxidizing agents, it was found that both H 2 O 2 and Na 2 S 2 O 8 are more efficient for isolating a stable fraction of SOC (Jagadamma et al, 2010). Therefore, in the present study, H 2 O 2 was used as the oxidizing agent in methods 2, 3a and 3b.…”
Section: Stable Soc Isolation Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…The SOC fraction resistant to chemical treatment was assumed to be stabilized due to strong chemical interaction with soil minerals. From a comparison of different oxidizing agents, it was found that both H 2 O 2 and Na 2 S 2 O 8 are more efficient for isolating a stable fraction of SOC (Jagadamma et al, 2010). Therefore, in the present study, H 2 O 2 was used as the oxidizing agent in methods 2, 3a and 3b.…”
Section: Stable Soc Isolation Methodsmentioning
confidence: 93%
“…The resistance of some constituents of plant residues to H 2 O 2 oxidation was proved when the light fraction (b1.6 g cm − 3 ) materials separated from the soil samples were exposed to H 2 O 2 oxidation. Among the land uses, the H 2 O 2 oxidation left behind a fraction of bleached plant residues with 30-56% of total OC (Jagadamma et al, 2010). The effect of tillage types on the stable SOC pool also depended on the methods used to isolate the stable SOC fraction.…”
Section: Stable Soc Recovery As Affected By Different Methodsmentioning
confidence: 99%
“…The NMR spectra consisted of between 20,000 and 50,000 acquisitions with a contact time of 3 ms and a pulse repetition time of 4 ms. The NMR spectra were divided into four chemical shift regions according to the chemical types of carbon as follows: 0-46 ppm (alkyl), 46-110 ppm (O-alkyl), 110-164 ppm (aromatic), and 164-190 ppm (carbonyl) [22,38]. The relative intensities of the chemical shift regions were determined by integration of the NMR spectra over given chemical shift ranges after phase and baseline corrections [22,38].…”
Section: Chemical Composition Of Lpommentioning
confidence: 99%
“…The NMR spectra were divided into four chemical shift regions according to the chemical types of carbon as follows: 0-46 ppm (alkyl), 46-110 ppm (O-alkyl), 110-164 ppm (aromatic), and 164-190 ppm (carbonyl) [22,38]. The relative intensities of the chemical shift regions were determined by integration of the NMR spectra over given chemical shift ranges after phase and baseline corrections [22,38]. Integration of the NMR spectra was done with OriginPro (Version 8, OriginLab Corporation, Northampton, MA, USA).…”
Section: Chemical Composition Of Lpommentioning
confidence: 99%
“…Thus, aromaticity of the oxidation residue decreased for Of and tended to increase for Qu. NaOCl treatment preferentially degrades lignin, and HF-treatment of NaOCl-treated subsoil samples removes virtually all lignin-derived phenols (Simpson and Hatcher, 2004b;Mikutta et al, 2005;Mikutta et al, 2006;Jagadamma et al, 2010). In contrast to Of, oxidation slightly decreased the relative contributions of O-alkyl C and carboxyl C in the Qu samples indicating that some oxidizable or labile C components were lost upon oxidation (Simpson and Hatcher, 2004b).…”
Section: Soil Organic Matter Changes Upon Oxidation and Black Carbon mentioning
confidence: 99%